Global trends in the health economics field of PD-1/PD-L1 inhibitors: A bibliometric and visualized study - Lai, Sicen; Xu, Licong; Zhang, Liang; Peng, Lanyuan; Li, Yixin; Liu, Yuancheng; Yu, Nianzhou; Chen, Wangqing; Huang, Kai (Frontiers in Pharmacology, 2023)
Inhibitors of programmed cell death protein 1 (PD-1) and its associated ligand (PD-L1) are widely used in cancer treatment. However, medical costs and benefits of PD-1/PD-L1 inhibitors need attention owing to differences in response rates among individuals. This study explored global trends in the health economics field of PD-1/PD-L1 inhibitors to enhance their worldwide development. Bibliometric analysis of all documents currently indexed in Web of Science Core Collection from inception to 2022 was performed. Publication year, authors, countries, institutes, and journals were analyzed by Bibliometrix package (version 3.2.1) in R (version 4.1.3). CiteSpace (version 6.1.R6) and VOSviewer (version 1.6.18) were used to analyze burst words, co-authorship of institutes, co-cited journals, and co-cited references, while figures were mainly drawn by Ggplot2 package (version 3.3.5) in R (version 4.1.3) and SCImago Graphica Beta (version 1.0.23). A total of 2020 documents related to the health economics of PD-1/PD-L1 inhibitors were identified, and 1204 documents met the selection criteria for inclusion in the study. A rapid increase in the number of publications since 2019 was observed, but this increase stopped in 2022, revealing research saturation in the field. Value in Health (166 publications, 13.79% of total documents) had the most publications, while New England Journal of Medicine (2890 co-citations) was the most co-cited journal. The USA was the leading contributor in this field with 506 publications and the top two productive institutes globally. The main hot topics included the cost-effectiveness of treatment with PD-1 and/or PD-L1 inhibitors, and the comparison between the cost-effectiveness of PD-/PD-L1 inhibitors and other drugs. There were substantial differences between developed and developing countries in the health economics field of PD-1 and/or PD-L1 inhibitors. The cost-effectiveness analysis of combined treatment with PD-1/PD-L1 inhibitors and other drugs warrants further attention. Findings from this study may provide governments and pharmaceutical companies with a strong reference for future research.